Applying the property of integer exponents, we know that (a^b)^c = a^(b*c). Therefore, we can rewrite (5^-3)^6 as 5^(-3*6).
Now, multiplying 517^1 and 10^-2, we use the property a^m * a^n = a^(m + n). This gives us 517^1 * 10^-2 = 517^(1-2) = 517^-1.
Therefore, the equivalent expression is 5^(-3*6) * 517^-1.
To solve this expression, we need to evaluate the exponents.
First, we simplify 5^(-3*6) = 5^-18. Using the property a^(-n) = 1/(a^n), we can rewrite this as 1/(5^18).
Now, we simplify 517^-1 = 1/517.
Therefore, the simplified expression is (1/(5^18)) * (1/517).
To compute this expression, we multiply the numerators and denominators separately:
(1 * 1) / (5^18 * 517)
= 1 / (5^18 * 517)
The final result is 1 / (5^18 * 517).
Apply the Properties of Integer Exponents to generate an equivalent expression to (5−3)6⋅ 51710−2
with only positive exponents, then solve the expression. (1 point)
(5−3)6⋅ 51710−2=
1 answer